DETERMINATION OF SUSPECTS IN CORRUPTION CRIMES BY POLICE INVESTIGATORS FROM A DUE PROCESS OF LAW PERSPECTIVE - Basar Achmad S Purba; Andi Maysarah; Dian Hardian Silalahi (NOMOI Law Review, 2026)
The extensive authority of Police investigators in determining suspects of corruption crimes often intersects with issues of arbitrariness and fundamental human rights protection. This study aims to analyze the reconstruction of suspect determination procedures based on Law Number 20 of 2025 and its juridical implications. As a theoretical and practical reference for legal practitioners, this research underscores the urgency of procedural compliance to ensure legal certainty. Employing normative legal research with statute and conceptual approaches , the discussion highlights a paradigm shift from broad discretion to mandatory scientific evidence, specifically requiring definitive state loss audits and